Actual and standard crop coefficients for semi‑natural and planted grasslands and grasses: a review aimed at supporting water management to improve production and ecosystem services - Pereira, Luís Santos (2023)
Natural and planted grasslands play a very important role in agriculture as source of various ecosystem services, including carbon sequestration and biodiversity, and are responsible for a large fraction of agricultural water use in rainfed and irrigated fields. It is, therefore, relevant to precisely know their water use and vegetation requirements with consideration of relevant climate, from extremely cold, dry, with long winter seasons, to tropical humid and hot climates, thus with a large variability of vegetation. Semi-natural grasslands are basically used for grazing and mainly refer to highland pastures and meadows, steppes, savannas, pampas, and mixed forest systems. The FAO method to compute crop (vegetation) evapotranspiration (ETc) through the product of a crop coefficient (K c ) by the reference evapotranspiration (ETo ) is adopted. The selected papers were those where actual ETc (ETc act ) was derived from field observations and ETo was computed with the FAO56 definition, or with another method that could be referred to the former. Field derived ETc act methods included soil water balance, Bowen ratio and eddy covariance measurements, as well as remote sensing vegetation indices or surface energy balance models, thus reviewed Kc act (ETc act/ETo) values were obtained from field data. These Kc act refer to initial, mid-season and end season (K c act ini , K c act mid , K c act end ) when reported values were daily or monthly; otherwise, only average values (K c act avg ) were collected. For cases relative to cold or freezing winters, data refer to the warm season only. For grasses cut for hay, K c act ini , Kc act mid , and Kc act end refer to a cut cycle. Kc act values rarely exceeded 1.25, thus indicating that field measurements reported did respect the available energy for evaporation. Overall, K c act mid for semi-natural grasslands in cold climates were lower than those in hot climates except when available water was high, with K c act mid for meadows and mountain pastures gener- ally high. Steppes have K c act mid values lower than savannas. Grasses commonly planted for hay and for landscape generally showed high K c act mid values, while a larger variability was observed with grasses for grazing. The collected K c act values were used to define standard Kc values for all grassland and grasses. Nevertheless, the tabulated Kc act are indicative values of K c to be used for actual water management purposes and/or irrigation scheduling of planted grasslands. It is expected that a better knowledge of the standard and/or indicative K c values for a wide variety of grasslands and grasses will support better management aimed to improve grass productivity and ecosystem services, including biodiversity and carbon sequestration